2021
DOI: 10.3390/ijerph18041490
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dry Carbon Dioxide Bathing on Peripheral Blood Circulation Measured by Thermal Imaging among Patients with Risk Factors of PAD

Abstract: Peripheral artery disease (PAD) is becoming a serious health problem of present times. It appears crucial to explore therapies that might help to restore blood flow or increase tissue oxygenation. The most effective methods of detecting early-stage changes in blood circulation in the extremities need to be identified. The aim of this study was to identify the effect of carbon dioxide (CO2) bathing on peripheral blood circulation measured by thermal imaging among patients with risk factors of PAD and ankle–brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…It has been suggested that the effects of CO 2 -enriched water on the subcutaneous microcirculation may be due to peripheral vasodilation as evidenced by increased parasympathetic and decreased sympathetic activity and that CO 2 foot bathing is clinically effective on salvage of CLI (Fontaine stage IV) limbs [16]. Recently, patients with PAD risk factors (ABI in the normal range or ABI indicating some or moderate arterial disease, ABI > 0.5) were shown to benefit from CO 2 therapy due to improvements in blood flow [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the effects of CO 2 -enriched water on the subcutaneous microcirculation may be due to peripheral vasodilation as evidenced by increased parasympathetic and decreased sympathetic activity and that CO 2 foot bathing is clinically effective on salvage of CLI (Fontaine stage IV) limbs [16]. Recently, patients with PAD risk factors (ABI in the normal range or ABI indicating some or moderate arterial disease, ABI > 0.5) were shown to benefit from CO 2 therapy due to improvements in blood flow [51].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the microcirculation promoting effect of CO 2 , angiography using CO 2 has been employed to monitor immediate response to endovascular therapy of PAD [29][30][31][32]. Since CO 2 water-bathing induces marked changes in body surface temperature, thermal imaging has also been used to measure the actions of CO 2 treatment in augmenting blood flow in patients with PAD [33]. Thus, CO 2 has not only been used as a therapeutic intervention for promoting blood flow but has also been exploited as a diagnostic tool for the detection and progression of PAD.…”
Section: Introductionmentioning
confidence: 99%
“…Авторами виявлено статистично достовірне збільшення під дією сухих СО 2 -ванн таких показників: рівня мікроциркуляції на 28,3 %, індексу флаксмоцій, що характеризує ефективність регуляції кровотоку в системі мікроциркуляції при набряках, на 36,8 %, амплітуди низькочастотних коливань на 13,9 % та зменшення амплітуди пульсових ритмів на 23,2 %. Також відзначено, що під впливом СО 2 -ванн відбувається зниження резерву капілярного кровотоку на 13,3 %, з достовірним збільшенням на 68,9 % часу напіввідновлення капілярного кровотоку і його швидкості, щільності капілярної сітки, зменшення кількості ліпідних включень, тривалості стазу, кількості сладжів і розмірів периваскулярної зони до нормальних показників [20].…”
unclassified
“…ЦД характеризується стійким рівнем підвищення АТ, а також порушенням діастолічної функції лівого шлуночка [20,21]. У таких хворих після комплексного лікування із застосуванням сухих вуглекислих ванн достовірно збільшувався середній показник співвідношення піків раннього та пізнього наповнення лівого шлуночка (близько на 10 %).…”
unclassified